THE ROLE OF COMPANY SIZE ON THE RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY, AUDIT QUALITY AND FIRM PERFORMANCE - Marsintauli, Frihardina; Murwaningsari , Etty; Husin, Hartini (Bina Nusantara University, 2025)
This study explores how company size affects CSR topics and audit quality and how they affect the performance of companies in the industrial and basic materials sectors listed on the Indonesia Stock Exchange from 2018 to 2021. There are 58 basic materials and industrial businesses that meet the sampling requirements, and they are the subjects of this quantitative study. Regression with moderate analysis is used in this study. According to this study, a company's size cannot mitigate the impact of CSR topics and audit quality on profitability. In the meantime, only the CSR topic substantially impacts profitability if audit quality and the CSR theme are only partially handled. The results of this study contribute to the body of literature on trade-off theory, which explains why businesses typically consider the trade-offs associated with a given activity. This study employs an innovative approach to quantifying the audit quality variable, using an index derived from the Indonesian Institute of Certified Public Accountants 2019. It seeks to investigate audit quality using dummy values or metrics used by public accounting firms, as well as the application and operations of these firms in delivering audit services to customers.